2020
DOI: 10.37398/jsr.2020.640148
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Text Summarization Techniques

Abstract: In recent years, an enormous amount of text data from diversified sources has been emerged day-by-day. This huge amount of data carries essential information and knowledge that needs to be effectively summarized to be useful. Hence, the main contribution of this paper is twofold. We first introduce some concepts related to extractive text summarization and then provide a systematic analysis of various text summarization techniques. In particular, some challenges in extractive summarization of single as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Then, each sentence is calculated to have a similarity value with the centroid based on cosine similarity, and then the feature values for each sentence are added together to get the sentence scores. A detailed review of techniques based on statistical approaches is discussed in [26] and [27].…”
Section: ) Statistical-based Methodsmentioning
confidence: 99%
“…Then, each sentence is calculated to have a similarity value with the centroid based on cosine similarity, and then the feature values for each sentence are added together to get the sentence scores. A detailed review of techniques based on statistical approaches is discussed in [26] and [27].…”
Section: ) Statistical-based Methodsmentioning
confidence: 99%
“…Various extractive and abstractive document summarization techniques have been proposed in literature based on evolutionary algorithms, neural networks, and clustering algorithms for single as well as multiple documents. Several recent surveys taking into account various effective models for text summarization on the basis of various parameters like relevancy, readability, redundancy, cohesion, coverage, precision, recall and accuracy are presented (Gambhir & Gupta, 2017;Lloret & Palomar, 2012;Nenkova & McKeown, 2012;Saggion & Poibeau, 2013;Torres-Moreno, 2014;Verma & Om, 2016;Verma & Verma, 2020a;Verma & Verma, 2020b). This section presents a brief survey of the most prominent and recent related works that contribute to the advancement of extractive document summarization for both single and multi-documents.…”
Section: Related Workmentioning
confidence: 99%
“…They have observed that many summarization techniques suffer from various challenges and hence effective summarization techniques are required. [7] Existing systems: Sentence Scoring based on Word Frequency: The model initially assigns weight to each word of the given corpus. With the help of the weights assigned, the model will assign a score for each sentence.…”
Section: Literature Reviewmentioning
confidence: 99%